Immunological Impacts of Diabetes on the Susceptibility of Mycobacterium tuberculosis - Birhanu Ayelign; Markos Negash; Meaza Genetu; Tadelo Wondmagegn; Tewodros Shibabaw (Journal of Immunology Research)
The interaction between diabetes and major world infections like TB is a major public health concern because of rapidly rising levels of diabetes. The dual burden of tuberculosis (TB) and diabetes mellitus (DM) has become a major global public health problem. Diabetes mellitus is a major risk factor for the development of active and latent tuberculosis. Immune mechanisms contributing to the increased susceptibility of diabetic patients to TB are due to the defects in bacterial recognition, phagocytic activity, and cellular activation which results in impaired production of chemokines and cytokines. The initiation of adaptive immunity is delayed by impaired antigen-presenting cell (APC) recruitment and function in hyperglycemic host, which results in reduced frequencies of Th1, Th2, and Th17 cells and its secretion of cytokines having a great role in activation of macrophage and inflammatory response of tuberculosis. In addition, impaired immune response and killing of intracellular bacteria potentially increase bacterial load, chronic inflammation, and central necrosis that facilitate bacterial dissemination and miliary tuberculosis. Understanding of the immunological and biochemical basis of TB susceptibility in diabetic patients will tell us the rational development of implementation and therapeutic strategies to alleviate the dual burden of the diseases. Therefore, the aim of this review was focused on the association between diabetes and tuberculosis, focusing on epidemiology, pathogenesis, and immune dysfunction in diabetes mellitus, and its association with susceptibility, severity, and treatment outcome failure to tuberculosis.